A Novel Polymer Based on Mtcu2+/Cellulose Acetate with Antimicrobial Activity - Guarda-Moraga, A; Rodriguez-Mercado, F; Bruna-Bugueno, J; Galotto-Lopez, M (2014)
Cellulose acetate (CA)/copper montmorillonite modified (MtCu2+) antimicrobial nanocomposites for food packaging containing 1, 3 and 5 wt.% nanoparticles were prepared by solution casting technique. X-ray diffraction (XRD) and transmission electron microscopy revealed the existence of intercalated and no intercalated clay form in the CA matrix. The thermal stability of the MtCu2+/CA nanocomposites was measured by TGA and DSC, which indicated that the nanocomposites were less thermally stable in comparison to CA pure. Mechanical testing of material did not show differences when MtCu2+ was added in CA. On the other hand, antimicrobial effect was observed for nanocomposites films, obtaining a 98% reduction against Escherichia coli. © 2013 Elsevier Ltd. All rights reserved.